Pendidikan Agama Islam di Era Post-Truth dan VUCA: Mengembangkan Kritisisme dan Keterampilan Pemikiran Kritis - Yusuf, M. (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2023)
This article discusses the role of Islamic Religious Education (IRE) in developing criticism and critical thinking skills in the post-truth era, which is part of the VUCA era. The circulation of unreliable information characterizes the post-truth era and is often spread through social media, creating a Volatile, Uncertain, Complex, and Ambiguous (VUCA) environment. In this context, IRE has an important role in helping students develop robust criticism and critical thinking skills to differentiate between facts and opinions and analyze information wisely. This study uses a literature review method to explore literature related to IRE in the post-truth era. The results of this study show that IRE can help students understand the importance of criticism and critical thinking in accordance with Islamic values and teachings in dealing with unreliable information. The development of criticism and critical thinking skills through IRE provides a strong foundation for students to filter information wisely, understand religion more deeply, and construct a more accurate and meaningful point of view in the post-truth era.